Environmental factors associated with juvenile idiopathic inflammatory myopathy clinical and serologic phenotypes - Jonathan C. Scalabrini; Adam I. Schiffenbauer; Payam Noroozi Farhadi; Rita Volochayev; Nastaran Bayat; Anna Jansen; Ira N. Targoff; Frederick W. Miller; Lisa G. Rider (BMC, 2022)
Abstract Background Environmental exposures have been associated with the juvenile idiopathic inflammatory myopathies (JIIM). We undertook a questionnaire-based study to evaluate patient-reported exposures as possible risk factors for JIIM. Findings One-hundred-seven patients with JIIM were enrolled in a myositis natural history protocol and completed environmental questionnaires. Frequencies of exposures in clinical and myositis-specific autoantibody (MSA) groups were examined. Patients with juvenile dermatomyositis (JDM) and juvenile connective tissue myositis (JCTM) more frequently received an immunization within 1 year of diagnosis compared to juvenile polymyositis (57.5 and 71.4% vs 0.0%, p ≤ 0.017). JCTM patients were more often underweight at diagnosis relative to JDM patients (42.9% vs 7.0%, p = 0.002). MSA-negative patients more frequently had gastroenteritis within a year of diagnosis compared to patients with anti-MDA5 autoantibodies (28.6% vs 0.0%, p = 0.032). Heavy exercise was more frequent in MSA-negative and anti-MDA5 groups compared to the anti-TIF-1 autoantibody group (42.9 and 35.3% vs. 9.0%, p ≤ 0.047). Medications received within 1 year of diagnosis were more frequent in MSA-negative patients relative to those with anti-MDA5 autoantibodies (92.9% vs. 52.8% p = 0.045). Being breastfed > 6 months was more frequent in MSA-negative patients (88.9%) compared to anti-TIF-1 and anti-MDA5 autoantibody groups (41.2 and 28.6%, p ≤ 0.036). Conclusions Certain environmental exposures prior to diagnosis differed among clinical and serologic subgroups of JIIM, suggesting additional exposures to be explored as possible risk factors for JIIM phenotypes.